Pengaruh Ketaatan Terhadap Perundangan, Sistem Pelaporan, Kualitas Sumber Daya Manusia dan Motivasi Kerja terhadap Akuntabilitas Kinerja Organisasi Perangkat Daerah Kota Palembang - Meta Dea Puspita; Zulkifli; Anggeraini Oktarida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to ascertain the impact of Work Motivation, Quality of Human Resources, Reporting Systems, and Legislation Compliance on the Performance Accountability of Regional Governmental Organizations (OPD) in Palembang City in 2024. The sampling technique that was used for this research is purposive sampling, with a population of 50 OPD in Palembang City and 32 Sample with a total of 183 respondents. Multiple linear regression is used in data analysis techniques for this study, which makes use of primary data and data hypothesis testing tools utilizing Statistical Product and Service Solutions (SPSS) software version 26. Partial hypothesis testing results indicate that each of the following variables has a partial impact on the variable Accountability for Organizational Performance: Quality of Human Resources, Reporting System, Compliance with Legislation, and Work Motivation.